Predicting Northern Bobwhite Habitat in Semiarid Rangeland Using Landsat Imagery - Jeffrey G. Whitt; Kelly S. Reyna (National Quail Symposium Proceedings, 2017)
Multiple studies have attempted to model northern bobwhite (Colinus virginianus) distribution using classified remotely sensed imagery in combination with pattern recognition software. These models tend to be more accurate in humid subtropical regions. To identify bobwhite habitat in subhumid and semiarid rangeland, we performed our own classification on 4 LANDSAT scenes of Clay County, Texas, from July and December 2015. Stands of mature little bluestem (Schizachyrium scoparium) provide excellent bobwhite nesting cover and could be identified using LANDSAT imagery. Habitat was scored from 0 to 1.0 based on estimated range health, presence of little bluestem, and presence of brushy cover. We compared habitat score with the results of breeding season call counts from 2014 and 2015 and found significant correlation. When used in combination with other landscape data, this approach can provide a regional context to inform conservation and management decisions.
Keywords: call counts; Colinus virginianus; northern bobwhite; GIS; habitat; Landsat; modeling; populations; remote sensing; Texas